Effect of Batik Wastewater Resulted from Biosorption Process to Blood Glucose Level on Carp (Cyprinus carpio) - Oktaviani, Safira Dwi; Lestari, Sri; Wibowo, Eko Setio (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
Chromium from the process of coloring batik has high toxicity to the organism. The biosorption method is the heavy metal adsorption process using inactive organisms to eliminate or decrease chromium in batik wastewater. In a polluted environment, fish can be in a stressful condition that requires energy to adapt to environmental changes; high energy requirements will stimulate an increase in blood glucose levels. Chromium exposure can increase the blood glucose level on carp (Cyprinus carpio). This study aims to determine the effect of batik wastewater resulted from the biosorption process exposure to the blood glucose levels. This study used 4 concentrations with 6 replications. Carp is placed in a mixed water tank with batik waste resulting from biosorption. The treatment of batik wastewater produced from the biosorption process concentration are of 0%v.v-1; 39,657%v.v-1; 26,438%v.v-1; and 13,219%v.v-1. Research shows that chromium was decreasing the results obtained at K0 are 68 mg/dL, at K1 is 132 mg/dL, K2 is 127 mg/dL, and at K3 is 116 mg/dL Batik wastewater resulted from biosorption process increasing the blood glucose level in fish and accelerates the rate of expenditure on fish The optimaly concentration of batik wastewater resulted from biosorption process are tried can Keyword : Batik wastewater, Biosorption, Blood glucose level, Carp